A chemical synthesis of porphobilinogen imitating the pathway proposed by Shemin for the biosynthesis: comparing inhibition studies with investigations of chemical reactivity - Bobal, Pavel; Chaperon, André; Neels, Antonia; Stoeckli-Evans, Helen; Neier, Reinhard (My University, 1999)
The synthesis of porphobilinogen and related compds. was reviewed with 78 refs. in this conference proceeding. Nature's pathways have been a strong motivation for synthetic chemists. Trying to imitate what has been shown or what is supposed to be a biosynthetic transformation always pursues several objectives: One evident goal is to obtain the natural product via the elegant way used in the natural process. The second not less important goal is to obtain insight into the mechanistic details of the biosynthetic pathway. Finally during the synthetic effort compds. are obtained which are potentially interesting as inhibitors of the natural process. Porphobilinogen, the second dedicated intermediate in the biosynthesis of 'pigments of life' synthesized following the mechanistic rationale proposed 30 yr ago by Shemin for the biosynthesis. Substances obtained during this synthetic effort and inhibitors esp. synthesized for our studies were tested in order to evaluate the different mechanistic proposals. This biomimetic approach allowed to guide at the same time the synthetic as well as the biosynthetic studies. [on SciFinder(R)]
Keywords: Pigments (review of the synthesis of porphobilinogen and related natural pigments with respect to biosynthesis); porphobilinogen synthesis biosynthesis review